Formula Optimization Of Orally Disintegrating Tablet Piroxicam with Superdisintegrant Pregelatinized Cassava Starch and Kollidon® CL - prayoga fery yuniarto (JCPS (Journal of Current Pharmaceutical Sciences), 2021)
Piroxicam is a non steroidal anti inflammatory drug (NSAID) has poor solubility with delayed onset of action. This can be overcome by created drug delivery systems capable of accelerating the disintegration and dissolution of the tablet piroxicam as Orally Disintegrating Tablets (ODT). The combined of pregelatinized cassava starch and Kollidon® CL as superdisintegrant is expected to generate ODT piroxicam with good physical properties. Optimization by simplex lattice design method was applied to optimize ODT piroxicam. The optimum area was determined using superimposed contour plot of hardness, friability, wetting time, disintegration time, and dissolution at 3 minute used Design Expert software. The result showed that optimum of ODT piroxicam with optimum physical properties was pregelatinized cassava starch 12,13 mg Kollidon® CL 5,87 mg.